La investigación de la anastilosis como herramienta en la conservación del patrimonio edificado. Caso de estudio “Plaza de San Francisco” Quito, Ecuador - Guijarro Taipe, Kleber Anibal (2023)
ABSTRACT: The present research is focused on analyzing the “ANASTYLOSIS” Technique (to return to its place those original elements) as a tool in the conservation of built heritage, to contribute with the methodological arguments, it was developed in the case of study that this technique was applied on the stone cladding of “San Francisco de Quito” square plaza in the year 2016, the technical-scientific methodology that was developed by the tutor and author of this research was based on guidelines established by the Metropolitan Institute of Heritage and applying theoretical - practical knowledge, that is to say, the present study begins from a personal experience; the work arose in order to carry out the archaeological project and build the subway station under the square. The research is based on the qualitative approach, the critical analytical descriptive method was used to contextualize this specific case, giving the necessary interest to the experience; experts were interviewed and personal file documents were collected, a methodological proposal for "PLANNED ANASTYLOSIS" was developed which will be useful in cases where it is necessary to move an asset for any circumstance from one site to another or to return it to the same site. This research was based and demonstrated that the use of this technique in the square was relevant, safeguarding its patrimonial essence, giving continuity to its current form, maintaining its memory and symbolic value. Obtaining a study to contribute to the knowledge of all those who are immersed in this activity. Keywords: Conservation, anastylosis, heritage, methodology, Square.